Membrane-based technologies for post-treatment of anaerobic effluents - Karahan, Huseyin Enis (2019)
Anaerobic digestion-based processes for converting wastewater into clean water and energy are attracting ever-growing industrial interest. However, apart from the microbial digestion step, current technologies require further progress from an integrated process point of view, including post-treatment steps. Anaerobic effluents normally undergo extensive post-treatment steps to meet stringent discharge standards, while valuable nutrients are rarely recovered. Additionally, a significant portion of the produced methane remains inevitably dissolved in the effluent, which is eventually released into the environment, causing economic loss and global warming concerns. To address these issues, several membrane-based technologies show significant promise. Here, we review current progress in membrane-based recovery of dissolved methane and nutrients, highlighting opportunities where membrane-based technologies can improve the post-treatment of anaerobic effluents. Lastly, we also share our perspectives for promising research directions and how to secure the competitiveness of membrane-based technologies for anaerobic wastewater treatment processes, focusing on current challenges for membrane development, biofouling mitigation strategies, and small-scale to large-scale implementation.